Approaches to monumental landscapes of the ancient Maya - Houk, Brett Alan 1967-; Arroyo, Bárbara; Powis, Terry G. (University Press of Florida, 2020)
"This volume brings together a wide spectrum of new approaches to ancient Maya studies in an innovative exploration of how the Preclassic and Classic Maya shaped their world. Moving beyond the towering temples and palaces typically associated with the Maya civilization, contributors present unconventional examples of monumental Maya landscapes. Featuring studies from across the central Maya lowlands, Belize, and the northern and central Maya highlands and spanning over 10,000 years of human occupation in the region, these chapters show how the word "monumental" can be used to describe natural and constructed landscapes, political and economic landscapes, and ritual and sacred landscapes. Examples include a massive system of aqueducts and canals at the Kaminaljuyu site, a vast arena designed for public spectacle at Chan Chich, and even the complex realms of Maya cosmology as represented by the ritual cave at Las Cuevas. By including physical, conceptual, and symbolic ways monumentality pervaded ancient Maya culture, this volume broadens traditional understandings of how the Maya interacted with their environment and provides exciting analytical perspectives to guide future study."--
Keywords: Maya; Kulturlandschaft; Landschaftsgestaltung; Landschaftsarchitektur; Urbanität; Mittelamerika; Mayas / History; Landscape archaeology; Cultural landscapes; Mayas; History; Aufsatzsammlung